Sensory integration disorders - a problem for children in the modern world - Nosek- Kozłowska, katarzyna (Rozprawy społeczne, 2024)
Abstract The aim of the article is to present the function and importance of sensory integration in everyday human functioning. Material and methods Analysis of the literature on the subject Results On the basis of scientific studies, a concise characterization of sensory integration processes and their dysfunctions was made. The combination and processing of the sensations are understood as the fundamental basis on which complex skills of acting, speaking and learning are developed. The article also describes how sensory difficulties affect a child's functioning in various situations, and provides tips for parents and guardians of children with sensory integration disorders. Conclusions Reflection on the issues raised indicates that understanding sensory integration disorders creates the possibility of effective support for children affected by this problem. Collaboration between parents, teachers and sensory therapy specialists is crucial. The introduction of appropriate educational, therapeutic and environmental strategies can significantly improve the quality of life of children with sensory integration disorders